2015
DOI: 10.1037/a0038376
|View full text |Cite
|
Sign up to set email alerts
|

Here today but not gone tomorrow: Incivility affects after-work and next-day recovery.

Abstract: This study examined the relation between daily incivility and afterwork recovery, hypothesizing that workplace incivility would have a negative effect on situational wellbeing, afterwork recovery experiences (psychological detachment and relaxation) and next-morning recovery level. Daily surveys were completed on 5 consecutive workdays by 175 employees in the legal industry. Multilevel analyses controlling for the daily number of hours worked showed that day-level incivility was negatively related to afterwork… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 64 publications
(116 reference statements)
6
50
0
Order By: Relevance
“…From the individual perspective, research findings indicate an adverse relationship between incivility and physical well-being (Hershcovis 2011;Nicholson and Griffin 2014). Nicholson and Griffin (2014) found that daily incivilities impact psychological detachment and relaxation after work.…”
Section: Incivilitymentioning
confidence: 98%
See 1 more Smart Citation
“…From the individual perspective, research findings indicate an adverse relationship between incivility and physical well-being (Hershcovis 2011;Nicholson and Griffin 2014). Nicholson and Griffin (2014) found that daily incivilities impact psychological detachment and relaxation after work.…”
Section: Incivilitymentioning
confidence: 98%
“…From the individual perspective, research findings indicate an adverse relationship between incivility and physical well-being (Hershcovis 2011;Nicholson and Griffin 2014). Nicholson and Griffin (2014) found that daily incivilities impact psychological detachment and relaxation after work. Additional individual impacts of incivility concern physical health (Githens 2011; Hershcovis 2011), psychological health (Hershcovis 2011;Miner and Eischeid 2012) or reactive perpetration responses as described by Gallus et al (2014).…”
Section: Incivilitymentioning
confidence: 98%
“…Oppression of powerless parties leads to low self‐esteem, anger, and fear, which manifests as bullying on one's own group over a period of time . The negative consequences from bullying often continue to affect individuals after they leave work and go home . Nurses who experience bullying may reduce work efforts and the quality of their work may suffer, which affects the quality of patient care they provide .…”
Section: Discussionmentioning
confidence: 99%
“…In-role job performance Figure 1 Conceptual model capabilities to learn and comprehend several routine tasks at the same time are limited by negative emotional responses (Foulk, Woolum and Erez 2016). Their skills of memorizing and using their own knowledge on the job are also impaired (Nicholson and Griffin 2015). As a result, employees who experience workplace incivility may decrease their inrole job performance.…”
Section: Innovative Job Performancementioning
confidence: 99%